Physicians, Assisted Suicide, and Christian Virtues - Reed, Philip A. (Christian bioethics, 2021)
The debate about physician-assisted suicide has long been entwined with the nature of the doctor-patient relationship. Opponents of physician-assisted suicide insist that the traditional goals of medicine do not and should not include intentionally bringing about or hastening a patient’s death, whereas proponents of physician-assisted suicide argue that this practice is an appropriate tool for doctors to relieve a patient’s suffering. In this article, I discuss these issues in light of the relevance of a Christian account of the doctor-patient relationship. I argue that Christians typically object to assist suicide independently of the doctor-patient relationship. I argue that a focus on the Christian virtues of charity, compassion, and humility helps to explain why doctors should not assist their patients in suicide.